PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM), GROSS PROFIT MARGIN (GPM) TERHADAP HARGA SAHAM PERBANKAN SYARIAH YANG TERDAFTAR DI BEI PERIODE 2021-2024 - Halimatul Sayyidah; Heidi Siddiqa; Dheri Febiyani Lestari (JURNAL EKONOMI PERJUANGAN, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM) on stock prices of Islamic commercial banks listed on the Indonesia Stock Exchange. This research employs a quantitative method with an associative approach. The data used are secondary data obtained from annual financial statements and stock prices for the research period. Data analysis was conducted using multiple linear regression, including classical assumption tests, coefficient of determination, F-test, and t-test. The results show that partially, ROA and ROE have no significant effect on stock prices. NPM has a significant negative effect, while GPM (after transformation) has a significant positive effect on stock prices. Simultaneously, these four independent variables significantly influence stock prices. The coefficient of determination indicates that part of the variation in stock prices can be explained by these profitability variables, while the remaining variation is influenced by other factors outside the research model. These findings suggest that investors pay more attention to operational efficiency indicators (GPM) than to ROA or ROE when making investment decisions in Islamic bank stocks. This study is expected to serve as a reference for companies to improve financial performance and for investors as a consideration in making investment decisions.